Detection Of Sheep And Goat Pox Viruses By Polymerase Chain Reaction - Kadam, A.S.; Tembhurne, P.A.; Ingle, V.C.; Kumar, P. Manesh; Dhok , A.K.; Kalorey , D.R. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Sheep pox and goat pox is a highly contagious viral disease of small ruminants and causes significant economic loss. Hence, the present study was undertaken to design PCR assay for the laboratory diagnosis of Sheep pox virus (SPV) and goat pox virus (GPV) from clinical samples.Thirteen scab samples from sheep and goat collected from suspected sheep pox and goat pox outbreaks reported at different parts of Maharashtra were used in this study. All the 13 scab samples were processed and inoculated through chorioallantoic membrane (CAM) route in embryonated chicken egg. Death of the embryo’s was observed between 9th to 11th day post inoculation with sheep pox suspected inoculum, where as death of the embryo’s occurred between 6th and 9th day post inoculation with goat pox suspected inoculum showing characteristics pock lesions in the form of grey white necrotic foci on CAM.The DNA was extracted from all the scab materials by phenol chloroform method with modifications. The purity and quantity of DNA was evaluated by nanodrop. The PCR was standardized for detection of SPV and GPV directly from the DNA isolated from scab material. All the 13 DNA samples of suspected cases were analyzed by PCR assay using published primer B68 and B69 of P32 gene. Of 13 clinical scab materials, 11 (84.62%) scabs showed the expected amplification of 390 bp represented by single band indicated the positivity for sheep pox and goat pox. The present PCR assay has considerable potential as a rapid and accurate diagnostic method for detection of sheep pox and goat pox from clinical samples over conventional techniques and can be employed in the phase of the outbreak for rapid confirmation.